DEVELOPMENT OF ICT LEARNING MEDIA BASED ON EXPERIENTIAL LEARNING APPROACH TO IMPROVE LEARNINGOUTCOMES CLASS V PKN SD SWASTA PAB 23 PATUMBAK - Asrul Asru; Abdul Hasan Saragih; Mukhtar Mukhtar (Sensei International Journal of Education and Linguistic, 2022)
Basically this research is intended to see the level of feasibility and effectiveness of developing ICT learning media in the form of interactive power points on PKN material. This research was conducted at PAB 23 Patumbak Private Elementary School. The subjects of this study were all fourth grade students at PAB 23 Patumbak Private Elementary School. This research method is Borg & Gall development research. The results showed (1) Based on the results of the analysis of ICT learning media products from experts it was declared very effective and feasible to use with the criteria of validity of material experts 85.00%, design experts 91.23%, and linguists 87.34%; 2) ICT learning media based on experiential learning is categorized as practical because ICT learning media based on experiential learning results from student responses have increased; and 3) ICT learning media based on experiential learning is said to be effectively used in learning with the assumption that students' understanding is higher when using ICT learning media based on experiential learning in the PKN learning process.